Ewing’s sarcoma of proximal femur: case report of extreme osteotomy with 3D-printed prosthesis for the reconstruction - Niu, Xiaoying; Tian, Wen; Liang, Xiaoxiao; Yao, Weitao; Zhang, Peng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Resection and reconstruction of malignant bone tumors at the proximal femur in adolescent patients has remained a clinical challenge. Considering the growth and development requirements of adolescents, there is no unified standard for the reconstruction of bone defects at the proximal femur. Here, we report a case of 3Dprinted titanium alloy customized prosthesis for the construction of proximal femoral bone defects in an adolescent patient with Ewing's sarcoma of the proximal femur.Case presentation: A 7-year-old female patient presented to a local hospital with left hip pain, and was diagnosed with Ewing's sarcoma on the proximal left femur. The patient received two courses of neoadjuvant chemotherapy before surgery according to the standard protocol. Considering growth and development problems associated with adolescents, we adopted a customized 3D-printed prosthesis of proximal femur for preservation of the femoral head and part of the femoral neck in the affected limb.Clinical outcomes, recorded after 12 months of follow-up, revealed excellent functional recovery and satisfactory functional scores of the affected limb, with no immediate complications.3D-printed prosthesis is a feasible method for preserving femoral head and reconstruction of bone defects in adolescents' proximal femur.